Wheat (Triticum aestivum L.) flour free lipid fractions negatively impact the quality of sponge cake. (15th January 2019) - Pycarelle, Sarah C.; Winnen, Kevin L.J.; Bosmans, Geertrui M.; Van Haesendonck, Ingrid; Pareyt, Bram; Brijs, Kristof; Delcour, Jan A.
Highlights: A high quality sponge cake has a high volume and a fine crumb structure. Defatting flour prior to sponge cake making improves product quality. Relocating flour lipids prior to sponge cake making decreases cake quality. Free flour lipids impact gas cell incorporation and stability in sponge cake batter. Abstract: The functionality of wheat flour lipids in sponge cakes prepared from flour, sugar, eggs and leavening agents only was investigated by altering their location or content in flour. Hexane (hex) or the more polar hexane:isopropanol (3:2 v/v) (hex:isoprop) were used to impact free flour lipid (FFL) or both FFL and bound flour lipid (BFL) fractions, respectively. Flour from which the FFLs were removed resulted in significantly improved cake volumes and crumb structures. Additional removal of part of the BFLs did not further impact cake quality. Prior contact of flour with hex:isoprop followed by gently removing the solvent broke native interactions between BFLs and starch or gluten and relocated more lipids than did hex. Cakes from flour with relocated lipids had coarse crumb structures. Our study demonstrates that FFLs and relocated flour lipids negatively impact sponge cake quality by disturbing air-liquid interface stabilization during mixing and the early phases of baking.